Smart contracts in the context of digitalization: the legal realities of world experience - Антошина, Ірина Володимирівна; Антошина, І. В.; Антошина, Ирина Владимировна; Antoshyna, Iryna V.; Клепікова, Ольга Вікторівна; Клепікова, О. В.; Клепикова, Ольга Викторовна; Klepikova, Olha V.; Klepikova, Olga; Гарагонич, Олександр Васильович; Гарагонич, О. В.; Гарагоныч, Александр Васильевич; et al. (Universidad del Zulia, 2021)
The development of digital technologies is forcing lawyers to analyze phenomena that have recently looked fantastic. This means that a phenomenon like smart contracts has ceased to be a theoretical idea of improving commodity monetary transactions and now needs a legal justification. In this article, we have analyzed smart contracts in terms of their belonging to digital technologies and the legal field, that is, how they can be equated with legal agreements, if they are their analogues, what application can it find given the legislation in the field of civil (contractual) law. The purpose of our study was to establish a link between smart contacts and their legal regulation, with the feature of smart contract implementation perspectives. The methodology used are systemic and formal-legal methods, as well as methods of analysis and synthesis. The results found highlight that a smart contract is a computer code that is entered into a blockchain network to execute a transaction, the usual expression of which is an agreement between the parties. From a legal point of view, smart contracts are only a part of ordinary agreements (contracts) under the practice of international and national law.

Розвиток цифрових технологій змушує юристів аналізувати явища, які нещодавно виглядали фантастично. Це означає, що таке явище, як смарт-контракти, перестало бути теоретичною ідеєю вдосконалення товарно-грошових операцій і тепер потребує юридичного обґрунтування. У цій статті ми проаналізували смарт-контракти з точки зору їх належності до цифрових технологій та правового поля, тобто як їх можна прирівняти до юридичних угод, якщо вони є їх аналогами, яке застосування вони можуть знайти з огляду на законодавство в галузі цивільного (договірного) права. Метою нашого дослідження було встановлення зв’язку між смарт-контрактами та їх правовим регулюванням з особливостями перспектив реалізації смарт-контрактів. Використовуються системні та формально-правові методи, а також методи аналізу та синтезу. Отримані результати показують, що смарт-контракт — це комп’ютерний код, який вводиться в мережу блокчейн для виконання транзакції, звичайним виразом якої є угода між сторонами. З юридичної точки зору смарт-контракти є лише частиною звичайних угод (контрактів) згідно з практикою міжнародного та національного права.
Klepikova O. Smart contracts in the context of digitalization: the legal realities of world experience / O. Klepikova, O. Harahonych, I. Antoshyna // Cuestiones Políticas. – Vol. 39. – Iss. 70. - Universidad del Zulia, 2021. – Р. 844-861.
Keywords: smart contracts; digitization; digital technologies; blockchain; digital assets; смарт-контракти; оцифровка; цифрові технології; блокчейн; цифрові активи; Research Subject Categories::LAW/JURISPRUDENCE